2014
DOI: 10.1261/rna.045781.114
|View full text |Cite
|
Sign up to set email alerts
|

Lariat intronic RNAs in the cytoplasm of Xenopus tropicalis oocytes

Abstract: We previously demonstrated that the oocyte nucleus (germinal vesicle or GV) of Xenopus tropicalis contains a population of stable RNA molecules derived from the introns of most expressed genes. Here we show that similar stable intronic sequence (sis) RNAs occur in the oocyte cytoplasm. About 9000 cytoplasmic sisRNAs have been identified, all of which are resistant to the exonuclease RNase R. About half have been confirmed as lariat molecules and the rest are presumed to be lariats, whereas nuclear sisRNAs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
142
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(149 citation statements)
references
References 52 publications
6
142
1
Order By: Relevance
“…Thus, intronic read levels from RNA-seq likely correlate with nascent embryonic transcription (Lee et al, 2013), and can be used to define zygotic gene timing. However, the recently discovered circular RNAs–which can contain unspliced introns–expressed in human oocytes and embryos (Dang et al, 2016) and stable intronic sequences (sisRNAs) in early frog embryos can be confounding factors (Talhouarne and Gall, 2014). …”
Section: Two Broad Categories Of Pre-gastrulation Vertebrate Embryo Dmentioning
confidence: 99%
“…Thus, intronic read levels from RNA-seq likely correlate with nascent embryonic transcription (Lee et al, 2013), and can be used to define zygotic gene timing. However, the recently discovered circular RNAs–which can contain unspliced introns–expressed in human oocytes and embryos (Dang et al, 2016) and stable intronic sequences (sisRNAs) in early frog embryos can be confounding factors (Talhouarne and Gall, 2014). …”
Section: Two Broad Categories Of Pre-gastrulation Vertebrate Embryo Dmentioning
confidence: 99%
“…Investigators found that intronic circRNAs can be duplicated in plasma and directly passed on to off-spring via mitosis, which hinted at the potential roles of intronic circRNAs in epigenetics and RNA-mediated inheritance. 29 Given the fact that the introns in the linear form are engaged in the mechanism to minimize tissue-inappropriate gene expression, the biological function of intronic circRNAs is close to being discovered in the near future. 30 Beyond regulating microRNAs, circRNAs may bind to and sequester RNA-binding proteins (RBPs) via their conserved seed matches, resulting in the formation of large RNA-protein complexes.…”
Section: Biogenesis and Functionmentioning
confidence: 99%
“…Thus, the lariat intron product offers a faithful, efficient, and direct alternative to mRNA for studying splicing genome-wide. Importantly, capturing the full landscape of introns, or the intronome, can provide insight into the production of not only mRNAs but also intron-encoded ncRNAs, such as small nucleolar RNAs, microRNAs, and some intronic circRNAs (Zhang et al 2013;Hesselberth 2014;Talhouarne and Gall 2014).…”
Section: Introductionmentioning
confidence: 99%